Phytogenic additives increase the performance and improve the tenderness of lamb meat: a meta-analytical and systematic review approach - Natalia Ingrid Souto da Silva; Patrícia de Oliveira Lima; Francisco Jocélio Cavalcante Souza; Marília Williani Filgueira Pereira; Rennan Herculano Rufino Moreira; Salenilda Soares Firmino; Thiago Luís Alves Campos de Araújo; Dorgival Morais de Lima Júnior (Semina: Ciências Agrárias)
This study aimed to verify how supply phytogenic additives (PA) can influence ruminal fermentation, digestibility, performance, carcass traits, and meat quality of lamb through a systematic review and meta-analysis. Data were extracted from 39 peer reviewed studies and analyzed using the F test when presented in a normal distribution, or the Kruskal-Wallis test when not presented in a normal distribution. Essential oils are most frequently used in the feed of lambs. The botanical species most used as source in the diet of lambs were Origanum vulgare (23.08%), Salvia rosmarinus (12.82%), and Allium sativum (7.69%). The PA supply didn't interfere (P>0.05) with the intake of crude protein and neutral detergent fiber (NDF) and increased (P = 0.011) crude protein digestibility from the lamb’s diet. There was an increase (P = 0.020) of 5.77% in the average daily gain, and an increase (P = 0.053) of 8.9% in the rib eye area of the carcasses of sheep fed PA. The supply of PA reduced (P = 0.047) 5.4% of meat shear force and increased (P = 0.041) 3.3% of meat cooking losses. We recommend the inclusion of phytogenic additives in the diet of lambs since it does not change nutrient intake, improves crude protein digestibility, and increases the average daily gain.